Dawn of diverse shelled and carbonaceous animal microfossils at ~ 571 Ma - Morais, Luana [UNESP]; Freitas, Bernardo T.; Fairchild, Thomas Rich; Clavijo Arcos, Rolando Esteban; Guillong, Marcel; Vance, Derek; de Campos, Marcelo Da Roz; Babinski, Marly; Pereira, Luiz Gustavo; Leme, Juliana M.; Boggiani, Paulo C.; Osés, Gabriel L.; et al. (Springer Nature, 2024)
The Ediacaran-Cambrian transition documents a critical stage in the diversification of animals. The global fossil record documents the appearance of cloudinomorphs and other shelled tubular organisms followed by non-biomineralized small carbonaceous fossils and by the highly diversified small shelly fossils between ~ 550 and 530 Ma. Here, we report diverse microfossils in thin sections and hand samples from the Ediacaran Bocaina Formation, Brazil, separated into five descriptive categories: elongate solid structures (ES); elongate filled structures (EF); two types of equidimensional structures (EQ 1 and 2) and elongate hollow structures with coiled ends (CE). These specimens, interpreted as diversified candidate metazoans, predate the latest Ediacaran biomineralized index macrofossils of the Cloudina-Corumbella-Namacalathus biozone in the overlying Tamengo Formation. Our new carbonate U–Pb ages for the Bocaina Formation, position this novel fossil record at 571 ± 9 Ma (weighted mean age). Thus, our data point to diversification of metazoans, including biomineralized specimens reminiscent of sections of cloudinids, protoconodonts, anabaritids, and hyolithids, in addition to organo-phosphatic surficial coverings of animals, demonstrably earlier than the record of the earliest known skeletonized metazoan fossils.